Response Evaluation Criteria in Cancer of the Liver version 5 (RECICL 2019 revised version). Issue 9 (25th July 2019) - Kudo, Masatoshi; Ikeda, Masafumi; Ueshima, Kazuomi; Sakamoto, Michiie; Shiina, Shuichiro; Tateishi, Ryosuke; Hasegawa, Kiyoshi; Furuse, Junji; Miyayama, Shiro; Murakami, Takamichi; Yamashita, Tatsuya; Kokudo, Norihiro
Abstract : Response Evaluation Criteria in Solid Tumors (RECIST) is inappropriate to assess the direct effects of treatment on hepatocellular carcinoma (HCC) by locoregional therapies, such as radiofrequency ablation and transarterial chemoembolization. Therefore, establishment of response evaluation criteria solely devoted to HCC is needed in clinical practice, as well as in clinical trials of HCC treatment, such as systemic therapies, which cause necrosis of the tumor. Response Evaluation Criteria in Cancer of the Liver (RECICL) was revised in 2019 by the Liver Cancer Study Group of Japan based on the 2015 version of RECICL, which was commonly used in Japan. The major revised points of the RECICL 2019 are as follows: (i) CEA and CA19‐9 have been newly added as tumor markers that should be recorded for use as criteria in the response evaluation for intrahepatic cholangiocarcinoma; (ii) the criteria now state that the details of molecular targeted therapy should be specified; and (iii) specific methods for overall evaluation are now described. Also, as an assessment of overall TE4 requires that TE4 is achieved in all nodules (even non‐target lesions), the same calculation methods described above are used. We hope this new treatment response criteria, RECICL, proposed by the Liver Cancer Study Group of Japan will benefit the HCC treatment response evaluation in the setting of daily clinical practice and clinical trials as well, not only in Japan, but also internationally.